Osteogenesis imperfecta: Diagnosis and management of an orphan disease in a Peruvian regional hospital. A case report - Centeno-Leguía, Dercy (2021)
Osteogenesis imperfecta is a rare autosome dominant disease in which there are anomalies in the synthesis of collagen affecting the connective tissue leading to multiple fractures. We present the case of a 38-week newborn from Pichari born of a cesarean section who presented respiratory failure. The patient presented crackles on the joints and was diagnosed on clinical grounds of osteogenesis imperfecta.